Sex Differences in Blood Pressure and Body Composition in Hypertensive Adults with Central Obesity - Riza Adriyani; Dody Iskandar; Ahmad Hendra Dana (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2021)
Regular exercise is recommended for adults experiencing hypertension with low and moderate cardiovascular risk. High intensity interval training (HIIT) is an efficient training method and has a better cardiometabolic protective effect. The purpose of this study was to determine sex differences in blood pressure and body composition after high intensity interval training. Twenty two adults with hypertension and central obesity (male n = 16, age 35.56 ± 4.56 years, waist circumference 98.85 ± 6.85 cm, systolic blood pressure 134.22 ± 2.86 mmHg, diastolic blood pressure 85.03 ± 6.58 mmHg) - (female n = 6, age 37.83 ± 5.46 years, waist circumference 95.09 ± 7.49 cm, systolic blood pressure 133.50 ± 6.47 mmHg, diastolic blood pressure 89.80 ± 5.94 mmHg) participated in a high intensity interval training (HIIT). The HIIT consisted of 3x4 minutes training at 77– 95% of maximum heart rate interspersed by 3 minutes of active rest at 64-76% of of maximum heart rate. The training was conducted three sessions per week for 10 weeks. Systolic blood pressure and diastolic blood pressure were significantly reduced in men. There was an improvement in body composition parameters, including a decrease in waist-to-hip ratio, visceral fat, and body fat mass in men (p 0.05). Waist circumference decreased in both men and women (p 0.05). It concludes that there are sex differences in cardiometabolic adaptation after HIIT.